Gastrin-releasing peptide receptor expression in gastrointestinal stromal tumours - M. Berndsen; F. Puls; A. Thornell; Y. Arvidsson; A. Muth; S. Lindskog; E. Elias (ESMO Gastrointestinal Oncology)
Background: There are limited treatment options for patients with advanced or metastatic gastrointestinal stromal tumours (GISTs) that lack mutations targetable by tyrosine kinase inhibitors (TKIs) or that have developed resistance to TKIs. Gastrin-releasing peptide receptor (GRPR) theranostics may offer a viable option in GISTs. However, the expression of the GRPR in GIST has not been extensively studied. Materials and methods: GRPR expression was evaluated using immunohistochemistry in two separate tissue microarrays from patients treated at Sahlgrenska University Hospital, one from the pre-TKI era (1983-2001) and the other from the post-TKI era (2014-2020). In total, 205 tumour samples were characterized as having low/none or moderate/high expression of the GRPR, and these were correlated with clinical characteristics and survival outcomes. Results: In total, 80% of the tumour samples exhibited moderate or high expression of GRPR. GRPR expression was not associated with gender, age, tumour location, or risk group, as defined by the modified National Institutes of Health (NIH) consensus criteria. Neoadjuvant treatment with TKI was correlated with low/none GRPR expression (P = 0.04). In patients who underwent surgery with curative intent and did not receive neoadjuvant treatment, GRPR expression was not associated with survival outcomes. Conclusions: This study is the first to investigate GRPR expression in a large cohort of GIST tumours. Our results demonstrate that most GIST tumours exhibit a moderate to high expression of the receptor, suggesting that GRPR theranostics could be a viable option for TKI-resistant GIST. Interestingly, tumours that were pretreated with TKI showed lower expression levels of GRPR, indicating a need for further studies to explore this finding.